Entre o violoncelo e o cavaquinho: música e sujeito popular em Machado de Assis - Idelber Avelar (Estudos de Literatura Brasileira Contemporânea)
The article discusses the tension between high culture, the emerging popular cul- ture, and the incipient mass culture through an analysis of the status of music in Machado de Assis’s work. Devoting special attention to a set of newspaper chronicles and to the stories “Um homem célebre” and “O machete”, the article postulates that Machado’s work was the first literary reflection on music as a pri- vileged cipher of nationality.